2017
DOI: 10.1111/pim.12420
|View full text |Cite
|
Sign up to set email alerts
|

Th17 cells and neutrophils: Close collaborators in chronic Leishmania mexicana infections leading to disease severity

Abstract: Cutaneous leishmaniasis caused by Leishmania mexicana is associated with an important inflammatory response. We here analysed the kinetics of Th17 cells and neutrophils in ear lobe lesions caused by Leishmania mexicana throughout 90 days of disease progression in susceptible BALB/c and semi-resistant C57BL/6 mice infected with 1 × 10 Leishmania mexicana promastigotes. Cells in the lesions were extracted and quantified by flow cytometry, whereas their distribution in the tissues in relation to the parasites was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 64 publications
2
30
0
Order By: Relevance
“…Neutrophils, through the release of inflammatory mediators and the formation of NETs, can drive inflammation [41]. L. mexicana was reported to elicit locally the formation of NETs and to favor the differentiation of Th17 cells recruiting more neutrophils to the lesion [7,42]. These 2 processes may participate in the development and persistence of L. mexicana lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils, through the release of inflammatory mediators and the formation of NETs, can drive inflammation [41]. L. mexicana was reported to elicit locally the formation of NETs and to favor the differentiation of Th17 cells recruiting more neutrophils to the lesion [7,42]. These 2 processes may participate in the development and persistence of L. mexicana lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is categorized as cutaneous (CL), mucocutaneous (MCL) and visceral leishmaniasis (VL), which is caused by over 20 species of the Leishmania (L) parasites . Cutaneous leishmaniasis (CL) with an estimated incidence of 1.5‐2 million cases annually is the most prevalent form of leishmaniasis . Although it is an endemic disease in 98 countries, approximately 75% of human CL cases are reported in only 10 countries including Afghanistan, Algeria, Brazil, Colombia, Costa Rica, Ethiopia, Iran, Sudan, Peru and Syria …”
Section: Introductionmentioning
confidence: 99%
“…Although some reports have suggested that IL-17 plays a pathogenic role in leishmaniasis (11-13), others showed that they play a protective role (7, 9, 10). Because we found that enhanced resistance of PTX3 -/- mice to L. major was not associated with superior IFN-γ response, we postulated that the enhanced resistance was mediated by increased IL-17 response.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, susceptibility has been associated with IL-4 and IL-10 production by Th2 cells, which are cytokines that deactivate macrophages and inhibit their ability to kill intracellular parasites (2, 6). Besides Th1 and Th2 cells, IL-17A-secreting Th17 cells have also been shown to mediate either host protection (7-10) or susceptibility (11-13) to leishmaniasis. However, the series of events that leads to the induction of Th17 responses in CL are unknown.…”
Section: Introductionmentioning
confidence: 99%